LearnMAPWay Certified Independent Study Program di PT Mitra Adiperkasa Tbk - Ramadhan, Fauzan Daffa; Karmudiandri, Arwina; Firnanti, Friska (Pusat Penelitian dan Pengabdian Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2022)
Independent study LearnMAPWay Certified Independent Study Program is an off-campus learning program organized by the Kampus Merdeka, which aims to provide knowledge related to the retail business world represented by PT Mitra Adiperkasa Tbk as the company that provides the education. The material to be delivered is related to operations, visual merchandising, and merchandising. This independent study program aims to provide students with knowledge about the world of retail business so that students can become entrepreneurs after completing their studies.